Dampak Perubahan Iklim Dalam Perekonomian Indonesia - Turnip, Christina Hotmatondini; Lumbansiantar, Krisna Sarinauli; Sinaga, Primawati; Nasution, Armin Rahmansyah; Harahap, Evi Syuriani; Dalimunthe, Muhammad Bukhori (CV. Rayyan Dwi Bharata, 2025)
Climate change has become a global phenomenon with significant impacts on the Indonesian economy, especially in vital sectors such as agriculture, fisheries, and infrastructure. This study aims to identify and analyze the effects of climate change on the Indonesian economy, as well as explore mitigation and adaptation solutions that can be applied. The method used in this study is qualitative with a descriptive approach, which relies on secondary data from relevant journals and articles. The results of the study indicate that climate change results in decreased agricultural yields, threats to the fisheries sector, damage to infrastructure, and increased public health risks. All of these in turn reduce productivity and economic stability. In addition, this study found that the uncertainty caused by climate change affects investment decisions, thereby hampering economic growth. The innovation of this study lies in the development of an economic model based on systems analysis that describes the interactions between economic sectors that are vulnerable to climate change, and provides recommendations for more effective adaptation and mitigation strategies according to the local context in Indonesia.